NIH/NCATS/GRDR(®) Common Data Elements: A leading force for standardized data collection - Rubinstein, Yaffa R. (Contemp Clin Trials, 2015)
The main goal of the NIH/NCATS GRDR® program is to serve as a central web-based global data repository to integrate de-identified patient clinical data from rare disease registries, EHR, clinical data and other data sources, in a standardized manner, to be available to researchers for conducting various biomedical studies, including clinical trials and to support analyses within and across diseases. The aim of the program is to advance research for many rare diseases and, by extension, common diseases as well. One of the first tasks toward achieving this goal was the development of a set of Common Data Elements (CDEs), which are controlled terminologies that represent collected data. The use of CDEs facilitates the integration of patient information. The GRDR CDEs have been the cornerstone of the GRDR repository, as well as of several other national and international patient registries. As a result many new opportunities for collaboration and networking are now available and being pursued. Most importantly, the establishment of the GRDR program has elevated the issue of data standardization and interoperability for rare disease patient registries, to international attention, resulting in a global dialog and significant change in the mindset of registry developers, patient advocacy groups, and other national and international organizations.